Non-intrusive electric power monitoring system in multi-purpose educational buildings - Fernando del Ama Gonzalo; Jose A. Ferrandiz; David Fonseca Escudero; Juan A. Hernandez (Institute of Advanced Engineering and Science, 2019)
Understanding the consumption patterns in a working space is important for evaluating the causes of energy wastage and for developing strategies towards specific energy reduction methods. The intent of metering systems in buildings is to provide adequate data that help improve building systems performance. The results of the analysis offer the potential to improve the energy efficiency of the building and reduce the operation costs. Researchers of Polytechnic University of Madrid and American University of Ras Al Khaimah have developed a metering and control system that processes and analyzes the digitalized signals. This system can collect, analyze and manage the electrical consumption in buildings. It is non-intrusive, can be easily deployed in electric boards and sends data to a central base station located away from the metering device. In this article the system is tested in an educational facility with a wide range of uses. The lighting fixtures, power outlets and HVAC devices are analyzed in offices, classrooms and architecture studios. This article concludes that energy audits for longer time periods help building managers understand device profiles, occupant behavior and environmental context.